2017
DOI: 10.1631/jzus.b1600370
|View full text |Cite
|
Sign up to set email alerts
|

Immune recovery after fluid resuscitation in rats with severe hemorrhagic shock

Abstract: Abstract:Objective: To investigate the effects of resuscitation with normal saline (NS), hypertonic saline (HTS), and hydroxyethyl starch (HES) on regulatory T cells (Tregs), helper T 1 (Th1)/Th2 and cytotoxic T 1 (Tc1)/Tc2 profiles in the treatment of hemorrhagic shock. Methods: Rats subjected to severe hemorrhagic shock were resuscitated for 30 min with NS (n=8), HTS (n=8), or HES (n=8); sham (n=8) and naive control (n=8) groups were used for comparison. Following fluid resuscitation, the whole shed blood wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 37 publications
0
5
0
Order By: Relevance
“…In acute inflammation, the activation of leukocytes often occurs after glycocalyx shedding, and it has been found that the resuscitation of colloidal fluids will further accelerate glycocalyx shedding, thereby exacerbating the inflammatory reaction [ 19 ]. However, a recent study showed that [ 20 ] HES can prevent the degradation and rupture of glycocalyx through reducing the plasma concentration of syndecan-1, thereby maintaining the integrity of vascular epithelium, preventing plasma leakage, and repairing vascular microenvironment damage caused by inflammation.…”
Section: Discussionmentioning
confidence: 99%
“…In acute inflammation, the activation of leukocytes often occurs after glycocalyx shedding, and it has been found that the resuscitation of colloidal fluids will further accelerate glycocalyx shedding, thereby exacerbating the inflammatory reaction [ 19 ]. However, a recent study showed that [ 20 ] HES can prevent the degradation and rupture of glycocalyx through reducing the plasma concentration of syndecan-1, thereby maintaining the integrity of vascular epithelium, preventing plasma leakage, and repairing vascular microenvironment damage caused by inflammation.…”
Section: Discussionmentioning
confidence: 99%
“…The imbalance of Th17/Treg has been suggested to be positively correlated with the degree of acute liver injury ( 35 ). The balance of Th1/Th2 is attributed to conversion to type 2 responses during HS development ( 36 38 ). DCs subject to HS were more inclined to polarize naive CD4 + T cells into Th2 and Treg cells, consistent with the clinically observed immunosuppressive phenomena in severe patients ( 39 ).…”
Section: Innate Immune Response To Hsmentioning
confidence: 99%
“…The number of CD4 + T lymphocytes was assessed using a FACSCalibur type flow cytometer and a tricolor fluorescent antibody labeling kit (BD, USA), as described by Yao et al (2017) and Zhang SG et al (2017). According to the reagent specification, each sample was processed in a TruCONT tube dedicated to flow cytometry.…”
Section: Detection Of Cd4 + T Lymphocytes By Flow Cytometrymentioning
confidence: 99%